Severe acute respiratory coronavirus virus 2 (SARS-CoV-2) seroconversion and occupational exposure of employees at a Swiss university hospital: A large longitudinal cohort study. (19th March 2022) - Martischang, Romain; Iten, Anne; Arm, Isabelle; Abbas, Mohamed; Meyer, Benjamin; Yerly, Sabine; Eckerle, Isabella; Pralong, Jacques; Sauser, Julien; Suard, Jean-Claude; Kaiser, Laurent; Pittet, Didier; et al.
Abstract: Background: The dynamics of coronavirus disease 2019 (COVID-19) seroconversion of hospital employees are understudied. We measured the proportion of seroconverted employees and evaluated risk factors for seroconversion during the first pandemic wave. Methods: In this prospective cohort study, we recruited Geneva University Hospitals employees and sampled them 3 times, every 3 weeks from March 30 to June 12, 2020. We measured the proportion of seroconverted employees and determined prevalence ratios of risk factors for seroconversion using multivariate mixed-effects Poisson regression models. Results: Overall, 3, 421 participants (29% of all employees) were included, with 92% follow-up. The proportion of seroconverted employees increased from 4.4% (95% confidence interval [CI], 3.7%–5.1%) at baseline to 8.5% [(95% CI, 7.6%–9.5%) at the last visit. The proportions of seroconverted employees working in COVID-19 geriatrics and rehabilitation (G&R) wards (32.3%) and non–COVID-19 G&R wards (12.3%) were higher compared to office workers (4.9%) at the last visit. Only nursing assistants had a significantly higher risk of seroconversion compared to office workers (11.7% vs 4.9%; P = .006). Significant risk factors for seroconversion included the use of public transportation (adjusted prevalence ratio, 1.59; 95% CI, 1.25–2.03), known community exposure to severe acute respiratory coronavirus virus 2 (2.80; 95% CI, 2.22–3.54), working in a ward with a nosocomial COVID outbreak (2.93; 95% CI, 2.27–3.79), and working in a COVID-19 G&R ward (3.47; 95% CI, 2.45–4.91) or a non–COVID-19 G&R ward (1.96; 95% CI, 1.46–2.63). We observed an association between reported use of respirators and lower risk of seroconversion (0.73; 95% CI, 0.55–0.96). Conclusion: Additional preventive measures should be implemented to protect employees in G&R wards. Randomized trials on the protective effect of respirators are urgently needed.